Teaching Strategies in Simulator-Based Courses: Basis for Faculty Development Program - Santi Edar, Anacris; Tongco, Alex; Arizalita, Benedicto; Baldomar, Lebron James; De Leon, Nathaniel; Manlimos, Jemar; Paño, Chereboy; Parami, Michael John (JPAIR Institutional Research, 2024)
Education should prioritize enhancing instruction quality through interactive methods to foster discovery learning and research skills, leading to more engaged students. This study evaluates faculty teaching methods’ effectiveness and their impact on student learning outcomes in a maritime education setting. Academic achievement, alongside learning styles and teaching strategies, is a focal point in educational research, delving into how learners engage with course material. The quantitative-descriptive research design involves maritime students, faculty, and administrators as respondents, aiming to explore their perceptions of teaching methods in simulator-based courses. Results indicate the integrative approach as the most utilized strategy, emphasizing a mean score of 4.65. The study underscores the significance of student-centered and active learning approaches to enhance educational outcomes. Findings offer valuable insights for educators and policymakers to develop effective teaching strategies tailored to maritime students’ needs.